The coins of India - Brown, C. J. (Cecil Jermyn), 1886-1945; Azariah, Vedanayagam Samuel, 1874-1945; Farquhar, J. N. (John Nicol), 1861-1929 (Salt Lake City, UT : Project Gutenberg, 2025)
"The Coins of India" by C. J. Brown is an informative historical account written in the early 20th century. This work serves as an introductory guide to the evolution of coinage in India, focusing primarily on the development of its historical significance as a reflection of economic, social, and political movements. The text appears to target both Indian readers and numismatic enthusiasts interested in understanding the rich heritage of Indian coins and their role in the broader context of history. At the start of the book, the author outlines the purpose of the volume and the methodology behind its creation. Brown emphasizes the need to generate interest among Indians regarding their ancient coinage, presenting coins as valuable historical artifacts rather than mere currency. He introduces the evolution of early Indian coinage from barter systems to stamped metal currency, highlighting notable forms such as punch-marked coins and the influence of various historical rulers in the development of coinage styles. Through this introduction, readers are invited to appreciate the coins not only as collectors' items but as important elements reflecting India's rich and complex history. (This is an automatically generated summary.)
Release date is 2025-03-06
Aaron Adrignola and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Numismatics -- India